Pengaruh Persepsi Siswa dalam Penerapan Sistem Full Day School terhadap Prestasi Belajar Mereka pada Mata Pelajaran Pendidikan Agama Islam - Permatasari, Ita; Kamal, Mustopa; Iwan, Cecep Darul (Jurnal Penelitian Pendidikan Islam, 2019)
The research article using survey method succeeded in proving a number of allegations as follows: (1) Perception of students of SMA Negeri 1 Ciamis in implementing the Full Day School system reached 72.55. This shows that students' perceptions in implementing the Full Day School system are at high qualifications because they are at 59.00 - 79.00; (2) The learning achievement of students of SMA Negeri 1 Ciamis in Islamic Religious Education subjects reached 72.20. This shows that the learning achievement of students is at a high qualification because it is at a high qualification because it is in the range of 59.00 -79.00; and (3) The effect of students' perceptions on the implementation of the Full day School system on student achievement in Islamic Education subjects in SMA Negeri 1 Ciamis is known by its R squared value of 0.001, meaning that the variable X affects the variable Y by 0.01 %. This shows that the influence between variable X and variable Y is very low because it is in the range of 0.00 - 0.20 and there are still other variables of 99.9% influence on the variable Y besides the X variable and is indicated by the correlation value of the author get the correlation coefficient between the X variable with the Y variable of 0.041> 0.05. Then H0 is accepted and the correlation coefficient value of 0.041 is classified as a very low correlation interpretation because it is in the range of 0.00 - 0.20.